Psychobiological responses at the beginning and the end of an academic year in teachers - Serrano, Miguel A.; Moya-Albiol, Luis; Salvador, Alicia (Anales de Psicología / Annals of Psychology, 2013)
Evidence shows that work stress increases risk of cardiovascular disease. Emotional, cardiovascular and endocrine responses are affected by day-to-day experience. Perceived stress, negative mood, heart rate (HR) and blood pressure (BP) increase in working periods. Cortisol (C) response is not so clear, there being contradictory results. The main purpose is to study stress markers in two working days in teachers. Moreover, we evaluate the role of gender in stress markers in 49 school teachers. Perceived stress, mood, BP, HR, and C were measured at the beginning and at the end of an academic year. Results show that psychological and heart rate responses to a working day were different at the end of the year, increasing, especially in men. BP and C responses descended at the end of the year. In conclusion, an academic year could affect negatively to the emotional state and heart rate of teachers. rcadorf eePr`rante dos jornadas laborales. Además se evaluó el papel del género en la respuesta de estrés en 49 profesores. Para ello, se midió la percepción de estrés, el estado de ánimo, la PA, la FC y el C al inicio y al final de un curso escolar. Los resultados muestran que las respuestas psicológicas y de FC fueron mayores al final de curso, especialmente en hombres. La PA y el C descendieron al final de curso. En conclusión, un curso académico podría afectar negativamente al estado emocional y a los niveles de FC de los profesores.